The association of shift work a nd coronary heart disease risk factors among male factory workers in Kota Bharu, Kelantan - Shafei, Mohd Nazri (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2007)
Modem society is changing quite rapidly in terms of economic, social and human behaviour. Consequently, various types of work schedules have been applied by organizations and companies. Working hours are extended to evenings and nights, as well as on weekends. Shift work is one of the work hour systems in which a relay of employees extends the period of production beyond the conventional 8-hour working· day. It potentially disrupts workers' normal biological or social diurnal rllyjhms or both. Shift work has been found to be associated with various health problems and there is a concern that shift workers are at higher risk to develop risk factors for coronary heart disease (CHD) such as hypertension, hypercholesterolaemia, obesity and diabetes mellitus (OM). The study was . undertaken to examine relationships between shift work and CHD risk factors, namely high blood pressure (BP), dyslipidaemia (either hypercholesterolaemia, hyper-low density lipoproteincholesterolaemia, hypo-high density lipoprotein-cholesterolaemia or hypertriglyceridaemia), high body mass index (BMI), diabetes mellitus and physical inactivity among male factory workers in a factory in Kota Bharu, Kelantan. This study was a cross-sectional study of 76 shift and 72 day workers from a factory in Kota Bharu, Kelantan. Data was collected through a questionnaire on psychosocial and lifestyle factors. Anthropometric and blood pressure measurement, fasting blood sugar and fasting lipid profiles analyses were obtained. Chi-square test was used to determine the significant difference in the prevalence for each CHD risk factors between the two worker groups. Multiple logistic regression was used to evaluate the odds ratio for each CHD risk factors associated with shift work. The prevalence of high BP, hypercholesterolaemia, hypertriglyceridaemia and body mass index (BMI) of equal to or more than 25 kg/m2 were significantly higher among shift workers compared to day workers. There was no difference in the prevalence of diabetes mellitus, hypo-high-density lipoprotein-cholesterolaemia, hyperhigh- density lipoprotein-cholesterolaemia and physical inactivity. When the shift workers were compared with the day workers, the adjusted odds ratio (OR) for high BP, BMI of equal to or more than 25 kg/m2 and physical inactivity were S.1 (95% Cl 1.4-56.8), 2.9 (95% Cl 1.3-6.1) and 7.7 (95% Cl 2.1-27.5) respectivL;)·· There was neither association of shift work with dyslipidaemia, nor with diabetes mellitus. There were positive association between shift work and high BP, BMI of equal to or more than 25 kg/m2 and physical inactivity which denotes a higher risk of CHD risk factors among shift workers compared to day workers.